Factor Influencing Young People Towards Unsafe Sexual Behavior (Shiksha Shastra Saurabh, 2024)
This study investigates the factors influencing young people undertaking special care at rehabilitation centers in Pokhara Valley to involve in unsafe sexual behaviors. A quantitative approach and a descriptive research design to achieve its goal, with 105 participants aged 18 and above selected through purposive sampling. Data were collected using a self-administered structured questionnaires focusing on socio-demographic, behavioral, and environmental factors. Analysis was conducted by using SPSS version 2020. Key findings of the study shows that, Participants below 20 years exhibited higher risky sexual behavior (70%) compared to older participants (100% risky behavior above 20 years; p = 0.072). Participants with sufficient pocket money engaged in 100% risky sexual behavior, while 68% of those with insufficient funds exhibited no risky behavior (p = 0.00). Similarly, in the case of pub attendance, all frequent pub-goers (100%) reported risky sexual behavior, while occasional visitors exhibited a 65% risk rate. Likewise, in the context of porn consumption, among participants who watched porn, 84% engaged in risky sexual behavior, compared to none among non-viewers or those uncertain about their viewing habits (p = 0.00). To address these risks, targeted interventions, including comprehensive sexual health education, accessible contraceptive services, and awareness campaigns, are essential. Efforts to promote open communication about sexual health and address societal taboos are crucial. Additionally, enhancing parental education and improving economic stability can further mitigate the prevalence of risky sexual behaviors among youths. The study emphasizes the need for multifaceted strategies to reduce health vulnerabilities and promote safer sexual practices.